Effect of Thickness Stretching on the Static Deformation and Dynamic Analysis of Composite Arches - Mahajan, Valmik M.; Ghumare, S. M.; Sairam, Velchuri; Petare, K. D. (Current Approaches in Engineering Research and Technology Vol. 5, 2024)
Aims: The present theory investigates the dimensionless vibration frequencies, deformations and stresses for antisymmetric composite and orthotropic arch. Study Design: In the present investigation, composite arches are examined using exponential-type of transverse shear and normal deformation effect. It considers the important effects of both transverse normal strain and shear deformation under the action of uniformly distributed loading (UDL). Place and Duration of Study: Department of Civil Engineering, Sanjivani College of Engineering, Kopargaon - 423601, Maharashtra, India, between Jan. 2023 to April 2024. Methodology: The associated governing equations are obtained using the principle of virtual work with Navier’s solution. The proposed composite arches are completely free from shear correction factors, the top and bottom surfaces satisfy the traction free zero end boundary conditions. Results: The proposed mathematical model obtained correct displacements, stresses, and vibration frequencies for composite shallow arches than other theories because prior literature did not consider the thickness stretching effect i.e. . Therefore, the proposed theory accounts for the effect of thickness stretching i.e. . The results are compared and validated through available literature. Conclusion: The proposed results will set the standard benchmark for researchers in the upcoming days about the design of such difficult and high-rise composite constructions.